Tisagenlecleucel in Children and Young Adults: Reverse Translational Research by Using Real-World Safety Data - Concetta Rafaniello; Carmen Ferrajolo; Mario Gaio; Alessia Zinzi; Cristina Scavone; Maria Giuseppa Sullo; Francesco Rossi; Liberato Berrino; Annalisa Capuano (MDPI AG, 2020)
Tisagenlecleucel has revolutionized the pharmacological approach of relapsed or refractory B-cell acute lymphoblastic leukaemialeukaemia in paediatrics. The safety profile of tisagenlecleucel still needs to be better defined. The aim of this study was a post-marketing evaluation of the safety of tisagenlecleucel through the analysis of the Eudravigilance database with focus on the paediatric population. From 2017 to 2020, one third of Individual Case Safety Reports referring to tisagenlecleucel (117/364) have been collected in paediatrics, on average nine year-old boys. Overall, 92% of the638 adverse events were serious and caused or prolonged hospitalisation. A total of 55 adverse events presented a fatal outcome, mainly due to progression of malignant neoplasm (N = 10; 18.2%), recurrence of acute lymphocytic leukaemia (N = 6; 10.9%) or occurrence of acute lymphocytic leukaemia (N = 5; 9.1%). Cytokine release syndrome was commonly reported after tisagenlecleucel infusion (54/638), followed by pyrexia (45/638) and hypotension (27/638). Only 18/638 events referred to neurotoxicity, none of them resulted in death. More than one third of cases (41/117) were suggestive of therapeutic failure. This first post-marketing analysis confirms pre-approval evidence of the safety profile of tisagenlecleucel in paediatrics. Since only a few years of marketing is available, further followed-up studies need to be performed to investigate longer-term safety of tisagenlecleucel.